Comparison Of The Effect Of Training Using Aid And Without Aid On The Speed Of 50-Meter Butterfly Stroke In Athletes Of Bina Tirta Swimming Club Medan - Waruwu, Nurhasanah Fitriani; Siregar, Abdul Hakim (JUPE : Jurnal Pendidikan Mandala, 2025)
This research also aims to find out how much influence training using equipment has on butterfly swimming speed in Bina Tirta Swimming Club swimming athletes, to find out how much influence training without aids has on butterfly swimming speed in Bina Tirta Swimming Club athletes. club, and to find out which form of training has a greater influence between training using aids and without aids on butterfly swimming speed in Bina Tirta Swimming Club swimming athletes. This research is experimental research. The data collection technique uses a 50 meter butterfly swimming test. The subjects of this research were 20 Bina Tirta Swimming Club athletes who were selected using purposive sampling techniques. This research was carried out for 6 weeks, 18 meetings with a frequency of exercise carried out 3 times a week. The data analysis technique uses inferential statistics with the t test. The results of research on the hypothesis show that 1) data on swimming speed using treatment using assistive devices obtained a calculated t value of 7.489 so it has an influence. 2) swimming speed data using treatment without using assistive devices obtained a value of 9.725 so it has an influence. 3) The results of the parametric test on the independent sample T-Test, obtained a significance (2-tailed) of 0.712 > 0.05 (no significant effect), so it can be concluded that training using fins aids and paddles , did not have a better effect compared to training without aids on swimming speed of 50 meters butterfly style in Bina Tirta Swimming Club Medan athletes The conclusion of this research is that the results of data analysis, hypothesis testing and discussion show that training without using assistive devices provides a more significant increase compared to assistive equipment in the 50 meter butterfly swimming speed of Bina Tirta Swimming Club Medan swimming athletes.